2017
DOI: 10.1016/j.jpsychires.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use disorder and suicide attempts in Iraq/Afghanistan-era veterans

Abstract: The objective of the present research was to examine the association between lifetime cannabis use disorder (CUD), current suicidal ideation, and lifetime history of suicide attempts in a large and diverse sample of Iraq/Afghanistan-era veterans (N = 3,233) using a battery of well-validated instruments. As expected, CUD was associated with both current suicidal ideation (OR = 1.683, p = 0.008) and lifetime suicide attempts (OR = 2.306, p < 0.0001), even after accounting for the effects of sex, posttraumatic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Marijuana use also predicted an increased likelihood of suicidal behavior as well as less of a decline in PTSD symptoms over the following year for those with elevated PTSD symptoms at baseline. These findings are in line with those of Kimbrel et al (), who found that the presence of a lifetime CUD diagnosis was associated with current suicidal ideation and with lifetime suicide attempts in a large sample of OEF/OIF veterans. Although Kimbrel et al () and colleagues found significant direct effects of CUD on suicidal behavior controlling for a PTSD diagnosis, this may be due to the cross‐sectional nature of their study or the treatment of CUD and PTSD as dichotomous variables as we found PTSD severity to moderate the relation between days using marijuana and suicidal behavior.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Marijuana use also predicted an increased likelihood of suicidal behavior as well as less of a decline in PTSD symptoms over the following year for those with elevated PTSD symptoms at baseline. These findings are in line with those of Kimbrel et al (), who found that the presence of a lifetime CUD diagnosis was associated with current suicidal ideation and with lifetime suicide attempts in a large sample of OEF/OIF veterans. Although Kimbrel et al () and colleagues found significant direct effects of CUD on suicidal behavior controlling for a PTSD diagnosis, this may be due to the cross‐sectional nature of their study or the treatment of CUD and PTSD as dichotomous variables as we found PTSD severity to moderate the relation between days using marijuana and suicidal behavior.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in line with those of Kimbrel et al (), who found that the presence of a lifetime CUD diagnosis was associated with current suicidal ideation and with lifetime suicide attempts in a large sample of OEF/OIF veterans. Although Kimbrel et al () and colleagues found significant direct effects of CUD on suicidal behavior controlling for a PTSD diagnosis, this may be due to the cross‐sectional nature of their study or the treatment of CUD and PTSD as dichotomous variables as we found PTSD severity to moderate the relation between days using marijuana and suicidal behavior. This study also extends the findings of a recent literature review conducted by Borges, Bagge, and Orozco () who concluded that there was strong evidence for an association between chronic marijuana use and elevated suicidal ideation and behavior.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Critics of marijuana legalization point to studies showing correlations between heavy cannabis use and suicide, depression, and mental health disorders. [29] However, such studies that demonstrate correlation have yet to confirm causation, which should be determined by a model’s ability to predict. [59] Although those reporting depression to SAMHSA have increasingly used marijuana since states began increasing access to regulated cannabis, [10] we observe no evidence that cannabis liberalization has predictive relationships with reports of any mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…Authors noted that despite validated assessments indicating worsening PTSD symptoms, participants reported feeling the substances improved symptoms. Authors of another study 8 found that Iraq/Afghanistan-era veterans who met criteria for cannabis use disorder had 1.7 times higher current suicidal ideation and 2.3 times higher lifetime suicide attempts compared to those who did not meet criteria.…”
Section: Introductionmentioning
confidence: 99%